2000
DOI: 10.1089/15246090050118152
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Model for the Recruitment of Diverse Women into Research Studies

Abstract: Researchers' understanding of recruitment and retention of study subjects is in its infancy. To address the dearth of information on the underrepresentation of diverse populations of women in research studies relating to health issues, the University of California, San Francisco (UCSF) National Center of Excellence in Women's Health completed a comprehensive examination of issues related to recruitment. By synthesizing data from literature reviews, focus groups, surveys, one-on-one interviews, and direct exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 19 publications
1
48
0
Order By: Relevance
“…This was achieved through the implementation of strategies that have previously proven effective in retaining women in similar research studies. 10, 11 We believe that a personalized approach to our participants was an important factor. We gave our participants individual attention, timely provision of feedback, and flexible appointment arrangements.…”
Section: Discussionmentioning
confidence: 97%
“…This was achieved through the implementation of strategies that have previously proven effective in retaining women in similar research studies. 10, 11 We believe that a personalized approach to our participants was an important factor. We gave our participants individual attention, timely provision of feedback, and flexible appointment arrangements.…”
Section: Discussionmentioning
confidence: 97%
“…Nonparticipation of marginalized groups may result from a variety of factors, such as economic constraints, social pressure, preconceived negative expectations, lack of trust, or other obstacles (B. Brown, Long, Gould, Weitz, & Milliken, 2000). A group's analysis of costs and benefits suffers if deliberation lacks diversity and reflects only or primarily the perspectives of culturally dominant group members (Streich, 2002).…”
mentioning
confidence: 99%
“…A number of studies have now shown that personalized recruitment strategies are effective for enrolling African Americans for cancer genetic studies [3, 19, 30]. One possible explanation for this is that personalized interactions allow the recruiter to anticipate and address potential barriers to participation such as fear of discrimination and mistrust of the medical establishment before such barriers form the basis of a negative response.…”
Section: Discussionmentioning
confidence: 99%